Unusual Swarm Activities in Toba Revealed by Temporary Seismic Network: A Preliminary Study - Mustika Nadia; A Arifullah; Yusran Asnawi; Didik Sugiyanto; Andrean Simanjuntak; Umar Muksin (Journal of Applied Geospatial Information, 2023)
In 2021, an unusual activities of earthquake swarm occurred for the first time in Lake Toba (Indonesia), one of the world's largest calderas. Despite the fact that the earthquakes occurred in a volcanic setting, the swarm activity could be connected to the tectonic activities from the Sumatra fault system. The swarm activity occurred at a very shallow depth and were felt by local peoples with the intensity of II-IV MMI. The aim of this study was to look into the characteristics of the earthquake swarm in the Toba Caldera using waveforms recorded by temporary stations between March and June 2021. In May and June 2021, a total of 26 seismic stations were deployed for two months. Automatic seismic wave detection is essential because it may be utilized in earthquake early warning systems and speeds up analysis of origin time, P-, and S arrival timings, and earthquake sites. We discovered characteristics of a non-swarm earthquake's spectrum waveform from low to high frequency, whereas the swarm earthquake generated high frequency seismograms. Furthermore, we successfully captured the hypocentre, which was spread in the SW - NE direction, and we may be able to identify the unknown geological system responsible for the swarm's activity.